A Retrospective Case Series in Fournier's Disease: And Its Emergency Management et Grafting Technique for Penis Coverage. (25th September 2022) - Tripodi, Domenico; Guastafierro, Antonio; Gagliardi, Federica; Amabile, Maria Ida; Lori, Eleonora; Cirocchi, Roberto; Pironi, Daniele; Forte, Flavio; Cannistra, Claudio; Sorrenti, Salvatore
Abstract : Fournier's gangrene is a necrotizing soft tissue infection of the genital, perineal, and perirectal areas. A primary isolated involvement of the penis is rare, but it can be affected in some circumstances. The purpose of this case series is to present the findings of our thirteen years' experience in the reconstruction of the penis in Fournier's gangrene and our full-thickness grafting technique to cover the penis rod. We retrospectively reviewed patient data who underwent a penis reconstruction following Fournier's gangrene in 2018. The data was analyzed to report the estimated percentage of complications, of patients with primary or secondary gangrene of the penis, the number of reinterventions, and finally the percentage of deaths or recovery. 23 patients underwent reconstruction with our technique of full-thickness skin graft. In all cases, the skin graft was harvested from the upper arm with an arrow shape mark. No further penile revision surgery was required, and neither patient complained about retraction, nor traction, or pain during erection. The donor site healed without any complications. We believe that the coverage of the penis using our grafting technique is safe, easily reproducible, and demonstrates excellent esthetic and functional results.